Perancangan Poros dan Rem Roda Depan Motor Honda Revo 110 CC - Miko Mikael; Kardiman Kardiman; Viktor Naubnome (Jurnal Ilmiah Wahana Pendidikan, 2022)
The motor is a unit consisting of various components that are integrated, called the vehicle. one that can support the running of the vehicle is the axle on the front wheel and don't forget to provide a braking system to make it safe when running. Likewise with this study which aims to analyze the design of the shaft, brakes for Honda Revo 110 cc motorcycles in order to meet the required criteria and applicable standards. The type of research used is experimental research, data collection is done directly. From the analysis of the calculations that have been carried out, the results obtained; Shaft Diameter = 17.1 mm, Allowable Normal Stress = 198.27 Mpa, Safety Factor = 2.9. Force on brake lever = 30 N and Diameter of caliper 83 mm